Information assurance handbook : effective computer security and risk management strategies - Schou, Corey (McGraw-Hill Education, 2015)
"Information Assurance Handbook: Effective Computer Security and Risk Management Strategies discusses the tools and techniques required to prevent, detect, contain, correct, and recover from security breaches and other information assurance failures. This practical resource explains how to integrate information assurance into your enterprise planning and IT strategy and offers an organizational approach to identifying, implementing, and controlling information assurance initiatives for small business and global enterprises alike"--